Technological competencies required for the intermediate and high school female teachers to use the interactive whiteboard within the classroom - Al-Qaraawi, Mashael Abdulrahman; Ghannam, Abu Bakr Yousef (Journal of Educational and Psychological Sciences, 2019)
The current research aimed at identifying the technological competencies required for intermediate and secondary school teachers to activate the use of interactive whiteboards in the classroom. To achieve this goal, the question of technological competencies for middle and high school teachers was answered to activate the use of the interactive whiteboard in the classroom. Based on the objective of the research and its questions، the researcher used the descriptive method for its relevance to the research. The sample included (40) teachers of the intermediate and secondary stage in Al-Fursan Private Schools for Girls in Riyadh who used the Smartboard in teaching. The researcher used the questionnaire to collect the necessary data to answer the study questions. The responses were analyzed using the following statistical methods: frequencies، percentages, arithmetic mean، Pearson coefficient to measure the validity of the internal consistency of the study instrument، and Vacronbach coefficient in order to measure instrument stability. The most important results of the research are that the members of the research sample have three design competencies needed to activate the use of the interactive whiteboard in the classroom to a high degree: the ability to design a lesson، master the techniques of evaluation and the ability to design activities، all using interactive whiteboard. The study also concluded that incentives were given to the teacher who uses interactive whiteboard in teaching, and also to design modern buildings for educational institutions in accordance with the requirements of presentation and use of the interactive whiteboard in the classroom. The study recommended the educating middle and secondary school teachers about the importance of using interactive whiteboard in the educational process at all levels، and also working on attracting highly qualified human cadres for the success of the interactive whiteboard.